2014
DOI: 10.1186/1472-6882-14-178
|View full text |Cite
|
Sign up to set email alerts
|

Brain areas involved in the acupuncture treatment of AD model rats: a PET study

Abstract: BackgroundAcupuncture may effectively treat certain symptoms of Alzheimer’s disease (AD). Although several studies have used functional brain imaging to investigate the mechanisms of acupuncture treatment on AD, these mechanisms are still poorly understood. We therefore further explored the mechanism by which needling at ST36 may have a therapeutic effect in a rat AD model.MethodsA total of 80 healthy Wistar rats were divided into healthy control (n = 15) and pre-model (n = 65) groups. After inducing AD-like d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 11 publications
1
24
0
Order By: Relevance
“…Apbb1 interacted with App to regulate Aβ generation from App 36 . Although numerous acupoints are used to treat Alzheimer's disease, ST36-SP6 has long been used in TCM as main acupoints to treat AD in clinical and animal studies 37 38 . This result suggests that EA stimulation results in comprehensive decreases in the expression of genes related to Aβ generation, especially Apbb1/App signaling, to induce significant neuroprotective effects in AD.…”
Section: Discussionmentioning
confidence: 99%
“…Apbb1 interacted with App to regulate Aβ generation from App 36 . Although numerous acupoints are used to treat Alzheimer's disease, ST36-SP6 has long been used in TCM as main acupoints to treat AD in clinical and animal studies 37 38 . This result suggests that EA stimulation results in comprehensive decreases in the expression of genes related to Aβ generation, especially Apbb1/App signaling, to induce significant neuroprotective effects in AD.…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture has shown some benefit effects on Alzheimer’s disease and Parkinson’s disease. Lu et al [ 32 ] showed that acupuncture at ST36 increases blood perfusion and glycol metabolism in certain brain areas in Alzheimer’s disease rat model by Positron Emission Tomography scanning. ST36 stimulation also induces neurogenesis in adult brains via the up-regulations of brain-derived neurotrophic factor, glial cell line-derived neurotrophic factor, basic fibroblast growth factor and neuropeptide Y, and the activation of the function of primo vascular system [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, there are many reports on electroacupuncture (EA) on ST 36, with one last year mentioning about the brain areas involved in the acupuncture treatment using ST 36 for an Alzheimer's disease model in rats. 53 Another interesting report 54 suggested that sciatic-nerve transection could reduce the total number of mast cells in ST 36 although the authors of that article did not mention the PVS or Kim's work.…”
Section: Discussionmentioning
confidence: 99%